The impact of foreign aid on low-income communities in Nigeria - Abolade, Temitayo (2019)
The research measured participation of community-based institutions in the application of foreign aid in the host community of Makoko, Nigeria, including inputs to the design of action plans, challenges in project implementation, and monitoring of those plans. Previous foreign aid and government expenditures on local communities in Nigeria were not judiciously utilized in achieving the required economic growth and development, so its socio-economic impact was minimal. This is because the impact of foreign aid on real sectors such as education, primary healthcare, and agriculture in similar low-income communities was not prioritized. Using the context of stakeholders’ theory, the present study investigated the perceptions of the impact of foreign aid on the Makoko Floating School (MFS) project in Makoko, a low-income community in Nigeria. Using a survey of 50 respondents within the Makoko waterfront community, this study included both the descriptive and qualitative method of analysis. The study findings support the view that foreign aid does have a positive and sustainable impact on the MFS project. This is largely because of stakeholder inclusion and participation. It is therefore imperative to actively integrate community-based institutions, foreign donors, and the local people to coordinate in project planning and execution towards achieving the benefits of foreign aid because the success of any foreign aid on local communities depends largely on the stakeholders’ management, collaboration, and commitment.